(untitled) (Journal of Computational Mathematics, 2022)
In this paper, a stochastic linear two-step scheme has been presented to approximate backward stochastic differential equations (BSDEs). A necessary and sufficient condition is given to judge the L_2-stability of our numerical schemes. This stochastic linear two-step method possesses a family of 3-order convergence schemes in the sense of strong stability. The coefficients in the numerical methods are inferred based on the constraints of strong stability and n-order accuracy (nN^+). Numerical experiments illustrate that the scheme is an efficient probabilistic numerical method.